Bedside Assessment of the Kidneys and Bladder Using Point of Care Ultrasound - Patrick J. Taus; Surya Manivannan; Ria Dancel (CINQUILL Medical Publishers Inc., 2022)
Given the contrasting echogenic characteristics of the urinary system and their easily identifiable distortion in response to numerous pathologic processes, the sonographic examination of the kidney and bladder can provide a wealth of clinical information [1, 2]. Although performed for decades as a referral and comprehensive radiologic study, improvement in the cost and performance of portable ultrasound devices has now made point of care ultrasound (POCUS) accessible to a growing number and variety of healthcare providers. The purpose of this review is to describe the technique and benefits of using POCUS to evaluate the kidneys, ureters, and bladder in common clinical scenarios.